PENGEMBANGAN MODUL ELEKTRONIK BERBASIS SOCIOSCIENTIFIC-ISSUE PADA MATERI VIRUS UNTUK MENINGKATKAN MINAT DAN KEMAMPUAN ARGUMENTASI - Sarah Rapma Kristina Sitanggang; Bernadetta Octavia; Anggi Tias Pratama (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to produce an electronic module based on socioscientific issues that is feasible to improve students' interest and argumentation skills. This research is development research with the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation). The product to be developed is an electronic module based on Socioscientific Issues on virus material. Data collection techniques used are interviews, observations, learning interest questionnaires. The resulting product is then validated by material experts and media experts, and a limited trial is carried out. Based on the results of the development of an electronic module based on socioscientific issues, it is concluded that the electronic module is feasible to be used for biology learning in terms of the assessment of material experts with an average value of 3.11 (very feasible) and the assessment of media experts with an average value of 3.77 (very feasible). And it is effective for increasing students' interest in learning as seen from the n-gains value of 0.55 with a moderate category and to improve students' argumentation skills with an n-gains value of 0.4 with a moderate category.